Effects of Ground Flaxseed on Growth Performance, Intestinal Morphology, and Meat Fortification with Fatty Acids in Finisher Male Broiler Chickens - Hassan Kermanshahi; Ali Daneshmand; Ali Javadmanesh; Salam Ibrahim (Poultry Science Journal)
The current study aimed to determine the optimum level of ground flaxseed needed to improve performance and enrich broiler meat with omega-3 fatty acids (n-3 FA). A total of 360 twenty-five-day-old male broilers (Ross 308) were reared on floor pens and fed diets supplemented with ground flaxseed during the finisher phase (d 25-45). The chickens were assigned to four treatments of six replicates as follows: 1) corn-soybean meal (CSM) based diet as control; 2) CSM supplemented by 3% ground flaxseed (flax3); 3) CSM supplemented by 6% ground flaxseed (flax6); 4) CSM supplemented by 9% ground flaxseed (flax9). Results showed that flax6 increased (P < 0.05) daily gain (ADG) and feed intake (ADFI), while it did not affect feed conversion ratio (FCR). In addition, flax9 decreased (P < 0.05) ADG and ADFI, and impaired (P < 0.05) FCR compared to the control group at the end of the experiment (d 45). Feeding flax6 increased (P < 0.05) polyunsaturated fatty acids (PUFA) and n-3 FA in breast and thigh muscles and lowered (P < 0.05) abdominal fat pad weight compared to the control group. Results revealed that feeding birds with ground flax6 improves growth performance, reducing fat depots and enriching meat with n-3 PUFA without negatively affecting gut morphology.